Murder on the left bank [large type] - Black, Cara, 1951- (An Aimee Leduc investigation, 2018)
In bestseller Black's fast-paced 18th Aimée Leduc investigation (after 2017's Murder in Saint-Germain), Léo Solomon, an elderly retired accountant in poor health, insists that lawyer Éric Besson, whose late mother was a friend of Léo's, deliver a notebook containing his handwritten confession and evidence of decades of police corruption to Paris's chief prosecuting attorney. Éric asks his 18-year-old nephew, Marcus, to act as courier, but Marcus never reaches his destination. When the boy's body turns up on the street two days later, the police rule the death a drug-related homicide. Éric asks his friend Aimée to investigate. Aimée, a new mother, reluctantly takes on the case only when she discovers that her late father is implicated by information in the now-missing notebook. When the killer threatens her daughter, Aimée is forced to accept help from the source she trusts least: her family.